PENDEKATAN WHITE BOX TESTING UNTUK MENENTUKAN KUALITAS PERANGKAT LUNAK DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN C++ - Sa’diyah Noor Novita Alfisahrin (LPPM Universitas Bina Sarana Informatika, 2012)
The development of software house have impact to the increment of software productivity circulating in the community, but the quality of software currently available is still questionable whether the software meet quality standards or not. White-box testing is a test that can be used to examine the internal structure of the program that access to the source code and can be done atany time in the software development cycle, so that the mistakes of the unwanted programs can be improved and can be a qualified software product. This research aimed to test the software using white box testing approach that can be used to find an unexpected error in the software are built. The research method in this research is the study of literature and experimental by testing theinternal structure of the software that include control flow testing, branch testing, basis path testing, data flow testing, and loop testing. By doing white box testing, the improvement of the software can be done at any time and can produce qualified software.Keywords: software testing, white box testing, software quality.